2008
DOI: 10.1348/174866407x214172
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function in acquired prosopagnosia: Lessons from a series of 10 patients with brain damage

Abstract: Acquired prosopagnosia varies in both behavioural manifestations and the location and extent of underlying lesions. We studied 10 patients with adult‐onset lesions on a battery of face‐processing tests. Using signal detection methods, we found that discriminative power for the familiarity of famous faces was most reduced by bilateral occipitotemporal lesions that involved the fusiform gyri, and better preserved with unilateral right‐sided lesions. Tests of perception of facial structural configuration showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
236
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(260 citation statements)
references
References 120 publications
(206 reference statements)
20
236
2
2
Order By: Relevance
“…These show reduced diagnosticity of the eye region of the face [38,39] and fewer ocular fixations on the upper face [40]. Studies with a similar paradigm to ours have also shown in some but not all prosopagnosic patients with occipitotemporal lesions a similar pattern, with selective impairment for eye configuration with spared processing of mouth configuration [29].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These show reduced diagnosticity of the eye region of the face [38,39] and fewer ocular fixations on the upper face [40]. Studies with a similar paradigm to ours have also shown in some but not all prosopagnosic patients with occipitotemporal lesions a similar pattern, with selective impairment for eye configuration with spared processing of mouth configuration [29].…”
Section: Discussionsupporting
confidence: 67%
“…The fact that aMCI patients had difficulty with all facial properties with brief viewing may reflect general reductions in processing speed, attention, or visual efficiency. Indeed, low-level factors like hemianopia reduce accuracy at limited duration, but unlike our aMCI patients, hemianopic patients achieve normal accuracy at unlimited duration [29] hence the important of trials that allow the subject more time.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Lesions to this region can cause prosopagnosia 25 , the inability to recognize the identity of familiar individuals, while leaving the ability to detect the presence of a face intact. Numerous studies that have employed fMRI adaptation paradigms have demonstrated the sensitivity of the FFA to differences in face identity 21,[26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Such lesion studies, combined with functional imaging studies in normal individuals, have demonstrated that regions of the posterior fusiform gyrus, the inferior lateral occipital cortex and the posterior superior temporal sulcus (STS) are involved in face processing (e.g., Allison et al, 1994aAllison et al, , 1999Barton, 2008;Kanwisher et al, 1997;Grill-Spector et al, 2004;Pitcher et al, 2009;Rossion et al, 2003;Sergent et al, 1992). Within these regions, that are part of the so-called 'core system' for face processing (Haxby et al, 2000), the fusiform gyrus seems to be especially important for processing facial identity.…”
Section: Introductionmentioning
confidence: 99%